High Spinal Anesthesia in a Patient Recently Submitted to an Epidural Blood Patch: A Case Report - Crisanto, Marcos Victor Silveira; Japolini, Katharina Lanza; Dall’Aqua, Camila Gomes; Delgado, Marina Ayres (Brazilian Journal of Case Reports, 2025)
Spontaneous intracranial hypotension (SIH) is a rare condition caused by cerebrospinal fluid (CSF) leakage, leading to orthostatic headache and associated symptoms such as nausea, vertigo, and visual disturbances. Epidural blood patch (EBP) is the first-line therapy for persistent symptoms. Neuraxial anesthesia after recent EBP poses unique challenges due to morphological changes in the epidural space. These changes, primarily caused by clot formation and subsequent fibrosis, can result in unpredictable epidural spread or excessive cephalad migration during spinal anesthesia. We report the case of a 30-year-old primigravida with SIH who underwent two EBPs during pregnancy and subsequently developed a high spinal block during elective cesarean delivery under spinal anesthesia. The patient experienced hypotension and bradycardia and sensitive blockade at C6, which were managed successfully, and both mother and newborn had an uneventful outcome. This case highlights the potential for erratic neuraxial block following recent EBP and provides a detailed discussion of the underlying mechanisms and management strategies. It underscores the importance of careful review of anesthetic history, individualized technique, and dosing adjustments. Evidence on the optimal timing and safety of neuraxial anesthesia after EBP is limited, and further research is needed to guide clinical decision-making in this setting.